Unusual mediastinal abscess to Pseudomonas aeruginosa in a cat in southern Brazil - Pandolfo, Gustavo Willian; Duranti, Gabriela Eduarda; Cristo, Thierry Grima de; Fornara, Maria Augusta; Ferraz, Sandra Maria; Casagrande, Renata Assis (Brazilian Journal of Veterinary Pathology, 2025)
A two-year-old male Siamese cat was submitted for necropsy. The animal had been anorexic, exhibited aggressive behavior, and had collided with objects around the house. Radiographic evaluation revealed an opaque abscess in the thoracic mediastinal region, and the cat died two days later. At necropsy, a slightly irregular abscess was found in the mediastinal region, varying from white to yellow, measuring 6 x 4 cm. The cut section contains yellow, irregular, and poorly defined areas interspersed with discrete red areas of firm consistency, along with hard areas. Histologically, the mediastinal abscess showed proliferation of poorly collagenized fibrous connective tissue, intense angiogenesis, and a marked infiltration of macrophages and epithelioid macrophages surrounding extensive areas of liquefactive necrosis with cellular debris, as well as abundant viable and degenerated neutrophils and areas of mineralized bone matrix formation. Aseptically collected fragments of the mediastinal abscess were submitted for bacterial culture, which isolated Pseudomonas aeruginosa. The anatomopathological and microbiological findings confirmed a diagnosis of mediastinal abscess due to Pseudomonas aeruginosa in a cat. We highlight the importance of both pathological and microbiological evaluation in such cases, expanding the differential diagnoses of mediastinal masses in cats.